Let’s Get To Know and Collaborate with Each Other: Develop Global-Multicultural Citizens in Today’s Interconnected World - Eteokleous-Grigoriou, Nikleia (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2026)
The society we live in has been described as the “Information Society ” because its infrastructure can be essentially founded on Information Technology; as well as multicultural society since it is composed of more than one ethnic group. The presence of diverse racial, cultural, economic and social groups; and people of different race, characterizes the configuration of our society. Given the above, there is a growing belief in the necessity of combining technology, education, and dialogue in the diminishment of social, economic and cultural gaps inherent within and among societies, and laying the foundations for peaceful coexistence. The Mediterranean Youth Technology Club, MYTecC, aims to achieve the above. It is a bridge building initiative amongst youth in Mediterranean Basin, the Middle East and the Arab World. Its goal is to use technology develop a human network with a particular focus: “Let’s get to know and collaborate with each other”.